Effects of water stress on the post-harvest quality of cut Lilium flowers - Mantilla Alarcon, Alfredo Gunther (2024)
The limited availability of water due to agricultural, industrial, technological, and urban expansion requires a greater effort to make its use more efficient and achieve substantial savings in ornamental productions without affecting the commercial value quality, and final presentation of flowers and plants. Water stress is an environmental factor that causes physiological effects in plants and accelerates the senescence of leaves and flowers on cut stems. Considering crop evapotranspiration (ETc), an alternative way to reducing water consumption in intensive crops is the use of controlled, restricted irrigation, coupled with the application of phytohormones in pre-harvest to mitigate the effects of water stress, i.e. 6- Benzylaminopurine (6-BAP). The objective of this study was to determine the quality and vase life of Lilium stems under restricted irrigation combined with phytohormones application. An experiment with four treatments was designed, concerning normal (NI, 100% ETc) or restricted irrigation (RI, 35% ETc) and with or without application of 6-BAP (300 ppm). A completely randomized ANOVA design with 6 repetitions per treatment was used. The vase life of cut Lilium flowers was not significantly affected (13.9 vs. 12.5 days under NI and RI respectively). The application of 6-BAP had no influence on vase life, but delayed the foliage yellowing and therefore reduced the rate of deterioration of the floral stem. Restricted irrigation and the application of phytohormones can be useful tools to improve the water use efficiency in lily crops.